2022
DOI: 10.3389/fmed.2021.823600
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Prognostic Factors of Pulmonary Fibrosis After COVID-19 Pneumonia

Abstract: BackgroundFew is known about the long-term pulmonary sequelae after COVID-19 infection. Hence, the aim of this study is to characterize patients with persisting pulmonary sequelae at follow-up after hospitalization. We also aimed to explore clinical and radiological predictors of pulmonary fibrosis following COVID-19.MethodsTwo hundred and 20 consecutive patients were evaluated at 3–6 months after discharge with high-resolution computed tomography (HRCT) and categorized as recovered (REC) or not recovered (NOT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 19 publications
7
39
0
1
Order By: Relevance
“…About half of the patients complained of respiratory symptoms at follow-up, and unlike what was assumed, we observed a discrepancy between respiratory symptom with lung volumes/alveolar-capillary diffusion and residual radiological parenchymal impairment. These findings were consistent with previous studies that observed only a weak correlation between post-COVID respiratory symptoms and functional-radiological parenchymal impairment at follow-up [ 13 , 14 , 15 ]. Indeed, there is still a lack of evidence regarding the mechanisms of post-COVID respiratory syndrome.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…About half of the patients complained of respiratory symptoms at follow-up, and unlike what was assumed, we observed a discrepancy between respiratory symptom with lung volumes/alveolar-capillary diffusion and residual radiological parenchymal impairment. These findings were consistent with previous studies that observed only a weak correlation between post-COVID respiratory symptoms and functional-radiological parenchymal impairment at follow-up [ 13 , 14 , 15 ]. Indeed, there is still a lack of evidence regarding the mechanisms of post-COVID respiratory syndrome.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have analysed CT parenchymal imaging of patients hospitalized for COVID-19 in a short- and medium-term follow-ups [ 2 , 3 , 13 , 14 , 15 , 19 , 20 , 21 , 22 ]. The methodological differences of these previous studies make a direct comparison among data difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors for post-COVID-19 pulmonary fibrosis associated with an individual and disease itself have been proposed in previous studies (Table 2). 6,7,11,12,14,16,[20][21][22][23][24] Alu median days from discharge to last follow-up: 9 day), fibrosis was observed in 44% of patients, and patients with fibrosis showed more frequent abnormal radiological features including interstitial thickening, air bronchogram, irregular interface, coarse reticular pattern, and parenchymal bands on worst CT images than those without fibrosis. 22 Although it is not known to be directly related to the development of fibrosis, cigarette smoking and alcohol consumption are potential risk factors for post-COVID-19 pulmonary fibrosis because of their association with the progression of severe pneumonia.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The common pattern of pulmonary interstitial lesions, also known as post-COVID-19 pulmonary fibrosis or COVID-19 pulmonary fibrosis-like ( 7 ), were ground glass opacities (GGOs), ground-glass attenuation and reticular abnormalities ( 8 ). At the same time, chest imaging showed bilateral diffuse interstitial lung disease among patients who complicated acute respiratory distress syndrome (ARDS) during acute phase ( 9 ). Relatedly, these survivals suffered from more serious ‘Long COVID' ( 10 , 11 ), a condition described by signs and symptoms of COVID-19 that last longer than 12 weeks and are not explained by an alternative diagnosis, with the most common symptoms of dyspnea, fatigue and ‘brain fog'.…”
Section: Introductionmentioning
confidence: 99%